EVIDENCES OF SCIENTIFIC MIRACLE OF AL-QUR’AN IN THE MODERN ERA - Dwi Sukmanila Sayska; Jani Arni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
One of the miracles of al-Qur’an is i’jaz ilmi, it’s meant the information of al-Qur’an about science which is then able revealed and proven in accordance with the development of science. I’jaz ilmi does not present itself, but should be explored and researched, so that the evidence of i’jaz ilmi can be more and more and grow over time. Scientists gave the parable is like a spring that never runs dry. Every time always comes new discoveries and scientific provisions which already hinted at al-Qur’an for 14 centuries ago as evidence of i’jaz. I’jaz ilmi later became a effective propaganda media, especially among scientists. Many cases found confession of scientists when they were able to prove the truth of which is informed by al-Qur’an. In addition, evidence of ilmi i’jaz is able to ward off external oblique view of Islam that al-Qur’an is man work, because when they know that what is described by al- Qur’an has been proved by modern scientific discoveries, and eventually they acknowledges that al-Qur’an is really the word of God